OPINION GAP: A STRATEGY IN IMPROVING STUDENTS’ SPEAKING ABILITIES - Andre Paulus Saleky (Leksema: Jurnal Bahasa dan Sastra, 2018)
The aims of this study were to find out how Opinion Gap Strategy can improve students speaking abilities and to know students’ responses on the implementation of Opinion Gap Strategy in speaking class. The study employed Classroom Action Research consisting of four steps, namely: planning, action, evaluation, and reflection. The instruments used to collect the data were tests, observations, and questionnaire. This study was conducted at class X4 of SMA Negeri 6 Ambon in 2016/2017 Academic Year at which the students were identified as having problem in speaking abilities. Based on the result of study, the implementation of Opinion Gap Strategy could help and motivate students to express their opinions, ideas, and feelings ona given topics. Furthermore, this strategy also provided positive effects since the students’ responses on the questionnaire sheets showed students’ agreement on the implementation of the strategy to improve their speaking abilities.